Skyrmion-electronics: writing, deleting, reading and processing magnetic skyrmions toward spintronic applications. (6th January 2020) - Zhang, Xichao; Zhou, Yan; Mee Song, Kyung; Park, Tae-Eon; Xia, Jing; Ezawa, Motohiko; Liu, Xiaoxi; Zhao, Weisheng; Zhao, Guoping; Woo, Seonghoon
Abstract: The field of magnetic skyrmions has been actively investigated across a wide range of topics during the last decades. In this topical review, we mainly review and discuss key results and findings in skyrmion research since the first experimental observation of magnetic skyrmions in 2009. We particularly focus on the theoretical, computational and experimental findings and advances that are directly relevant to the spintronic applications based on magnetic skyrmions, i.e. their writing, deleting, reading and processing driven by magnetic field, electric current and thermal energy. We then review several potential applications including information storage, logic computing gates and non-conventional devices such as neuromorphic computing devices. Finally, we discuss possible future research directions on magnetic skyrmions, which also cover rich topics on other topological textures such as antiskyrmions and bimerons in antiferromagnets and frustrated magnets.